Costume : Performing Identities through Dress - Shukla, Pravina, 1968- (Book collections on Project MUSE., 2015)
What does it mean to people around the world to put on costumes to celebrate their heritage, reenact historic events, assume a role on stage, or participate in Halloween or Carnival? Self-consciously set apart from everyday dress, costume marks the divide between ordinary and extraordinary settings and enables the wearer to project a different self or special identity. Pravina Shukla offers richly detailed case studies from the United States, Brazil, and Sweden to show how individuals use costumes for social communication and to express facets of their personalities.